Clinical and functional differences between right and left stroke with and without contralateral spatial neglect - Sinikka Tarvonen-Schröder; Tuuli Niemi; Mari Koivisto (FOUNDATION REHABILITATION INFORMATION, 2022)
Objective: To examine the clinical and functional characteristics associated with contralateral spatial neglect in right compared with left subacute stroke, and to investigate the correlations between neglect severity and stroke severity, functional ability and outcome.Methods: Cross-sectional study comparing neurological impairment and disability. The same data-set was used in part 2 of this study.Results: Contralateral neglect was present in 79.7% of right stroke and 68.3% of left stroke rehabilitants, and was, on average, equally mild. Left stroke rehabilitants with neglect had higher stroke severity, cognitive and total disability and dependence level and more impaired sphincter control than right stroke rehabilitants with neglect, while the occurrence of depression, motor and sensory impairment was similar. Rehabilitants with neglect, irrespective of stroke side, had higher stroke severity, cognitive, motor and total disability and dependence level than rehabilitants without neglect.Conclusion: In left and right stroke rehabilitants with equally mild neglect, those with left stroke had higher stroke severity, cognitive and total disability and dependence level. Neglect severity correlated with right or left stroke severity and functional ability, moderate to severe neglect correlated significantly more with functioning. Neglect severity was independently associated with functional outcome in right stroke.